Fixing Transnational Drug Policy: Drug Prohibition in the Eyes of Comparative Law. (20th October 2019) - Colson, Renaud
Abstract : Drug prohibition allows us to study over a significant period of time how penal provisions framed at a supranational level flow, settle, and unsettle across different countries. At a time of growing doubt about the benefit of criminalization of drug use, it also provides a case‐study as to how epistemic communities may rely on comparative research to identify best practices and promote them as normative alternatives in the face of a long‐entrenched legal dogma. In order to explore these issues, this article looks at the UN drug control system from the perspective of comparative law. It shows how the concept of legal transplant provides a useful tool to understand the limits of transnational criminal law designed on a global scale to tackle the 'drug problem', and it clarifies the various types of legal comparison that might contribute to addressing this failed transplant.